Gedanken über die Bestimmung von Räumen gleichen sozialgeographischen Verhaltens - Hartke, Wolfgang (ERDKUNDE, 1959)
The author reviews some theoretical aspects of social geography that have arisen from the work done in his departments at the Universities of Frankfurt and Munich. The most important contributions are analysed to point out the possibilities of finding, limiting, and typifying regions of equal socio-geographical behaviour. Most examples are taken from rural geography, but urban geography is re presented, too. The fundamental idea is that physical and cultural geofactors, which both have objective, quasi-stable qualities, do not characterize regions of equal socio-geo graphical behaviour. These are, in fact, determined by attitude and valuation of social groups in rather limited areas. They govern the working process in its regional differentiation. This working process is partly reflected by the landscapial differentiation, which offers some explanation of the socio-geographical dynamics of a region. This is useful for many purposes, especially for applied geography and regional planning.